Menanamkan Karakter Percaya Diri Siswa Melalui Kegiatan Pengembangan Diri Seni Tari Di SMP Negeri 2 Bukittinggi - Indah Septiani; Fuji Astuti; Herlinda Mansyur (SENDRATASIK UNP, 2019)
This article aims to describe the planting of students' self-confidence characters through the self-development of dance in Bukittinggi 2 Public Middle School. This type of research is Qualitative Descriptive Research. The object of research is students of class VII and VIII in Bukittinggi Middle School 2 who participated in Self Development as many as 12 people. The research instruments were researchers as teachers and observers as well as school principals and art and culture teachers at Bukittinggi Middle School 2. Furthermore, data is collected by observation, interviews and documentation. The results of the study showed that the planting of students' self-confidence characters carried out during 6 meetings went well and smoothly. It turned out that through the Pasambahan dance it was able to instill the character of self-confidence of students in Bukittinggi Middle School 2, where in the Pasambah Dance itself students were required to focus and have self-confidence in performing each of the movements of Pasambah with the complexity of martial arts movements at the opening of Pasambahan Dance, for road techniques for carano carrier and motion at the closing of Pasambah Dance and the use of changing floor patterns, so that students' confidence can be embedded through this Pasambah Dance. It was proven at each meeting that students experienced an increase in self-confidence by referring to six indicators of self-confidence and categorization, namely self-confidence in good categories, feeling self worthy in good categories, not relying on other people with good enough categories, not boasting with categories good, not hesitant in the good category and have the courage to act in a fairly good category, so that at the end of the process students are shown in the opening ceremony of the seminar at IAIN Bukittinggi also looks good. Thus it can be concluded that the Pasambah Dance that was passed on the Self Development of Dance was able to instill the Student's Confident Character in Bukittinggi Middle School 2 well.